2010
DOI: 10.1007/s10926-010-9248-2
|View full text |Cite
|
Sign up to set email alerts
|

Disability Management Outcomes in the Ontario Long-Term Care Sector

Abstract: Across facilities, there was no evidence that modified duty arrangements were associated with lower disability compensation expenditures and there was mixed evidence that modified duty was associated with a lower burden of disability. In this setting, disability days managed by modified duty arrangements were not accurately documented in worker's compensation claim records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Other work-related risk factors for musculoskeletal injuries include overloading of joints (A. Nelson et al, 2003), wholebody vibration (Maikala & Bhambhani, 2006), overexertion from manual materials handling activities, and physical demands of work such as lifting frequency; number of trunk, knee, and shoulder flexions per hour; and twists and motions per hour (Lipscomb, Cameron, & Silverstein, 2008;Lloyd et al, 2008). Health care workers have a high risk of work-related disability due to WMSD, partly because of excessive workloads, patient handling, and physical aggression by residents, especially in the institutional health sector (Mustard et al, 2010).…”
mentioning
confidence: 99%
“…Other work-related risk factors for musculoskeletal injuries include overloading of joints (A. Nelson et al, 2003), wholebody vibration (Maikala & Bhambhani, 2006), overexertion from manual materials handling activities, and physical demands of work such as lifting frequency; number of trunk, knee, and shoulder flexions per hour; and twists and motions per hour (Lipscomb, Cameron, & Silverstein, 2008;Lloyd et al, 2008). Health care workers have a high risk of work-related disability due to WMSD, partly because of excessive workloads, patient handling, and physical aggression by residents, especially in the institutional health sector (Mustard et al, 2010).…”
mentioning
confidence: 99%
“…shown that musculoskeletal demands such as awkward postures, heavy lifting and repetitive movements negatively influence health (Bowers et al, 2003;Mustard et al, 2010;Pope, 2002;Roelen et al, 2007) and compromise well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Formal caregivers who reported a worse physical health perception had been working at the same institution for a longer period of time and had chosen this job for circumstantial reasons. As caregiving is a difficult job, with continuous musculoskeletal demands ( Jorgensen et al, 2009;Mustard et al, 2010;Smith & Baughman, 2007;Wilner, 2000) it is expected that it leads to caregivers' exhaustion ( Jorgensen et al, 2009;Wilner, 2000) and therefore, influence their perception of physical health. Moreover, caregivers who chose this job for circumstantial reasons have less motivational factors that negatively influence their behaviors, satisfaction, performance and job commitment (Tadin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful return-to-work coordination often depends on the ability to develop and implement a modified work plan that fosters recovery and rehabilitation but is also responsive to concerns and agreeable to the injured worker, the healthcare provider, and employer [16][17][18]. Despite the acknowledged benefits of workplace job accommodation to prevent sickness absence and reduce disability costs, studies have provided a recurring theme that job modifications are often poorly planned or executed in the workplace [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%